Implementasi LISA (Lihat Sampah Ambil) Program Makassarta’ Tidak Rantasa di Universitas Muhammadiyah Makassar - Hardianti Hardianti; Andi Muh Fikram Aditama Wildam; Nasrulhaq Nasrulhaq (Research and Development Agency Ministry of Home Affairs, 2017)
In reaching the Makassarta’ Not Rantasa’ (MTR), the Mayor of Makassar launched the LISA program (See the Trash and Take) in order to improve the cleanliness of the City. LISA is a derivative of Makassarta’ Not Rantasa’ public policy. This movement is the beginning to instill awareness of all citizens of Makassar City to care about the environment. However, looking at the reality of LISA implementation to the community has not been fully implemented properly. Therefore, the purpose of this research is to know the implementation of LISA toward Makassarta’ Not Rantasa’ program in awaking the importance of environmental cleanliness at Makassar Muhammadiyah University. The type of research used is a qualitative approach with descriptive research type using field research which aim to find facts about cleanliness in Makassar City, case study Makassar Muhammadiyah University. The results concluded that LISA program has not fully solved the garbage problem. To realize this program is supported also by other programs such as; garden hallway and garbage bank. The level of awareness of students to see the waste in the University of Muhammadiyah Makassar is also still lacking.